PF-10 Antimicrobial Resistance of Bacterial Strains Isolated from Layer Chicken on Poultry Village in North Lombok, West Nusa Tenggara, Indonesia - Alfiana Laili Dwi Agustin; . Kholik (Hemera Zoa, 2018)
Egg of Layer chicken is one of the main income and protein sources at Kampung Unggas in North Lombok. Kampung Unggas is Village which produce and supply egg for Three Gili as tourist destination in Lombok Island. They are Gili Trawangan, Gili Meno, and Gili Air. Farmers in Kampung Unggas are used several antibiotics for treating infections in poultry. The use of antimicrobials in chicken farm in Lombok Island can facilitate the antimicrobial resistant. Antimicrobial resistance (AMR) is not a recent phenomenon, but it is rising concern for both public and animal health [1].Chicken farmers in the study region are mostly family run and they don’t have good bio security and sanitation procedure. Knowledge of farmer on antimicrobials resistance are very low and they are often kept free ranged among other animals and people. This means that the risk of contamination to food and water from bacteria and other pathogen infected poultry is high. Many farmers in Kampung unggas have other poultry, mostly ducks, in the same enclosure as their Chickens. The closeness between many different animals and humans as well as the short distance to temperate water, without cleaning or buffering stages, is a concern both in disease transmission and antibiotic resistance development [2].In Indonesia, study on 35 sampels of broiler meat and chicken meat from 9 distric in Bogor showed that prevalence E. coli 97.4% from broiler meat and 71.1% chicken meat resistance with Ampisilin, Enrofloksasin, Teterasiklin, Eritromisin, Streptomisin, Gentamisin, Kloramfenikol, Sefatotin, Trimetoprim-Sulfametoksasol, Nalidixid Acid [3]. According by [4] from 66 layer chicken 44% and from 35 broiler chicken 97.1% E. coli resistance with Oxytetracycline Hydrochloride, Chloramphenicol, Dihydrosreptomycin, Sulfadimethoxine Kanamycine and Aminobenzyl-penicillin.Based on thus facts, it is very important to know prevalence and antimicrobial resistance on bacterial strains isolated from Layer chicken and knowledge of antibiotic resistance among farmers on Poultry Village in North Lombok, West Nusa Tenggara Province, Indonesia for effective medical treatment of humans and poultry. Further, knowing the reasons for chicken farmers to treat their animals and which types of antibiotics chosen can facilitate prevention of antimicrobial resistance development.